Motivation and mobile devices: exploring the role of appropriation and coping strategies - Ann Jones; Kim Issroff (Association for Learning Technology, 2007)
There has been interest recently in how mobile devices may be motivating forces in the right contexts: for example, one of the themes for the IADIS International Conference on Mobile Learning in 2007 was ‘Affective Factors in Learning with Mobile Devices' (http://www.mlearningconf.org). The authors have previously proposed six aspects of learning with mobile devices in informal contexts that might be motivating: control over learners' goals, ownership, fun, communication, learning-in-context and continuity between contexts. How do these motivational features relate to theoretical accounts of what motivates people to use mobile devices and learn in technology- rich contexts? In this exploratory paper we consider two different candidates for such theoretical approaches. One is technology appropriation–the process by which technology or particular technological artefacts are adopted and shaped in use. Two different approaches to technology appropriation are discussed in order to explore the relationship between the different aspects of appropriation and motivation; that of Carroll et al. and that of Waycott. Both appropriation frameworks have been developed in the context of using mobile devices, but neither has a specific focus on learning. By contrast, the second theoretical approach is Järvelä et al.'s model of coping strategies, which is specifically concerned with learning with technologies, although not with mobile technologies in particular. The paper draws on case-study data in order to illustrate and discuss the extent to which these two approaches are helpful in informing our understanding of the motivating features of using mobile devices for informal learning.